A sequential mixed model research design: design, analytical and display issues - Cameron, Roslyn (eContent Management Pty Ltd, 2009)
A new era in research methods is emerging and has been quickly lauded by several emerging authorities in the field of mixed methods research. Like the mythology of the phoenix, mixed methods research has arisen out of the ashes of the paradigm wars to become the third methodological movement (Cameron & Miller 2007). The fields of applied social science and evaluation are among those which have shown the greatest popularity and uptake of mixed methods research designs. This article provides a brief overview of the rise of mixed methods research, its usage in business and management fields and its relationship to the philosophy of pragmatism. Typologies of mixed methods research designs are discussed and a case study of sequential mixed model research design in the human resource development (HRD) field is presented. Issues related to design, analytical processes and display arising from utilising this particular mixed method research design are discussed. As a consequence, the article contains several Tables and Figures which exemplify display options that may assist those researchers who are considering utilising a mixed method research design.